2023
DOI: 10.3390/d16010026
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Potential of Nicotiana glauca Aqueous Extract on Seed Germination and Seedlings of Acacia gerrardii

Abdelmalik M. Abdelmalik,
Thobayet S. Alshahrani,
Abdulaziz A. Alqarawi
et al.

Abstract: Nicotian glauca is a noxious invasive shrub in Saudi Arabia, and it is well known for its harmful impact on biodiversity, competing with native plants using various strategies. Among their strategies is their allelochemical activity, i.e., the use of chemicals to dominate and compete. The present study aims to evaluate the allelopathic potential of N. glauca aqueous extracts from leaves, flowers, and twigs on Acacia gerrardi seed germination and seedling growth. Petri dishes containing extracts from N. glauca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…Additionally, the IC 50 values of the extracts used against the hypocotyls/coleoptiles and roots of M. sativa and L. multiflorum (in this present research) showed species-dependent inhibitory activity (Table 3). Other researchers have documented similar results regarding the speciesand dose-dependent allelopathic properties for the extracts of Anredera cordifolia, Nicotiana glauca, Callistemon viminalis, and Aegle marmelos [45][46][47][48].…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, the IC 50 values of the extracts used against the hypocotyls/coleoptiles and roots of M. sativa and L. multiflorum (in this present research) showed species-dependent inhibitory activity (Table 3). Other researchers have documented similar results regarding the speciesand dose-dependent allelopathic properties for the extracts of Anredera cordifolia, Nicotiana glauca, Callistemon viminalis, and Aegle marmelos [45][46][47][48].…”
Section: Discussionsupporting
confidence: 61%